2015
DOI: 10.1097/ajp.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in the Dopamine Receptor 2 Predict Acute Pain Severity After Motor Vehicle Collision

Abstract: Objectives: Dopaminergic signaling is implicated in nociceptive pathways. These effects are mediated largely through dopamine receptors and modulated in part by dopamine transporters. This study tests the hypothesis that genetic variants in the genes encoding dopamine receptor 2 (DRD2) and the dopamine active transporter (SLC6A3) influence acute pain severity after motor vehicle collision (MVC). Methods: European Americans presenting to the emergency department (ED) after MVC were recruited. Overall pain int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 62 publications
2
29
1
Order By: Relevance
“…In addition, it has been demonstrated that genetic variants of the gene DRD2 are linked to responses to acute painful stimuli after a motor vehicle collision within the middle‐aged population . Patients with the rs6276 A/A genotype express lower pain than do individuals with the A/G or G/G genotype . Overall, these data suggest that genetic variants of SLC6A3 and DRD2 can alter acute pain expression.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, it has been demonstrated that genetic variants of the gene DRD2 are linked to responses to acute painful stimuli after a motor vehicle collision within the middle‐aged population . Patients with the rs6276 A/A genotype express lower pain than do individuals with the A/G or G/G genotype . Overall, these data suggest that genetic variants of SLC6A3 and DRD2 can alter acute pain expression.…”
Section: Introductionmentioning
confidence: 90%
“…Pain tolerance and expression after identical noxious stimuli vary widely among individuals. Genetic factors may contribute to various responses to painful stimuli . The involvement of monoamine neurotransmitters, especially serotonin and norepinephrine, in pain expression is well established, and clinical trials have shown that serotonin norepinephrine reuptake inhibitors are effective against neuropathic pain .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations